Analisis Tingkat Kepuasan Pasien Rawat Inap Terhadap Mutu Pelayanan di Rumah Sakit Hidayah Boyolali - Fatas, Ivan Ardo; , M. Farid Wajdi, Ph.D; , Soepatini, S.E., M.Si., Ph.D (2017)
Hidayah Boyolali hospital is one private hospital in Central Java province. From the data obtained in February 2014 the number of visits for inpatients at the hospital had decreased and continued to decline until May 2014. The decline in the number of patient visits can occur either because the patients were less satisfied or dissatisfied with the services which provided at the hospital. This study aims to analyzed inpatient satisfaction for the quality of services at the Hospital Hidayah Boyolali and identify which attributes should be main priority and maintained. This research method is descriptive qualitative using Servqual. The population in the study were all inpatients, whereas the number of samples in this study were 50 people. Gap between customers' service expectations and their perceptions analized by using Cartesius cart. The results of the analysis with the Cartesius cart shows two attributes are included in quadrant A, the first is the doctors and nurses are fast in providing the needed services, the second is the doctors and nurses are listened patiently to the patient's complaints. Two of these attributes should be a priority by Hidayah hospital in an effort to improve their service quality, because these two attributes are considered very important by patients, but instead it's not yet in line with patients expectations. Keywords : Service Quality, Satisfaction, Cartesius Cart